Analisis Sistem Penilaian Kinerja Terhadap Motivasi Kerja Karyawan Instalasi Radioterapi di RS Hasan Sadikin Bandung - Silvia Octaviani; Agus Alamsyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Performance appraisal is a very important factor for measuring and evaluating employee performance in a company.. This study aims to analyze the importance of the performance appraisal system on the work motivation of employees of the Radiotherapy Installation at RSHS Bandung. This study uses a descriptive qualitative method, which is naturalistic through interviews with five informants, namely the Secretary, Radiographer, Nurse, and Medical Records Staff. The results of this study indicate that the performance appraisal system implemented in the Radiotherapy Installation uses the e-Kinerja application of Permenpan No.6 of 2022. The performance appraisal system helps the employee performance evaluation process objectively and in a structured manner, based on individual performance indicators set by the Head of the Radiotherapy Installation. It is also known that employee work motivation is influenced by psychological needs, a positive work environment, training and development, compensation, support and appreciation from superiors. A transparent performance appraisal system has a positive influence on employee work motivation supported by the percentage level of successful performance achievement in the first quarter of 2022 which started from 91.6% and increased to 93% in the fourth quarter of 2022. This figure of 93% is stable until the fourth quarter of 2023. This study concludes that a well-implemented performance appraisal system can increase employee motivation and productivity. Suggestions for radiotherapy installation management are to increase supervision of employee time discipline, such as imposing strict sanctions on employees who violate working hours.